PENGARUH TOTAL ASSETS TURNOVER TERHADAP RETURN ON ASSET PADA PT PINDAD (PERSERO) PERIODE 2013 – 2017 - Mega Novitta; Hadi Juwanda (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2023)
This research conducted to determine the influence of Total Assets Turnover (TATO) toward Return on Asset (ROA) at the PT PINDAD (Persero) period of 2013 to 2017. This research used descriptive research with quantitative approach for the method. The analysis technique used here are normality test analysis, Pearson correlations analysis, coefficient of determination, and simple regression analysis. Hypothesis testing is done by using the t-test. The results of Pearson correlations analysis is 0,593 which means both of variable has a strong enough correlation. The coefficient of determination (R square) is 0,352 which means TATO has an influence 35,2% toward ROA, and the results of simple regression analysis indicates that every increase 1% of TATO then ROA will increase by 0,101%. The results of hypothesis testing (t-test) thitung : 1,276 < ttabel : 3,18245 which indicates H0 accepted it means TATO does not have a significant effect towards ROA. For recommendations, PT PINDAD (Persero) should be expected to maintain and continue to control the stability of Total Assets Ratio, so Return On Asset will continue increase. It is important for the company to survive in the future.